Dinamika dan Kontestasi Moderasi Beragama di Kalangan Guru Pendidikan Agama Islam Kota Pekanbaru - Asmuri, Asmuri; Masbukin, Masbukin; Pallawa, Alimuddin Hassan; Hanafi, Imam (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
PAI teachers are an important part of supporting the success of the Religion moderation program that is being echoed by the Ministry of Religious Affairs today. It would be a problem if PAI teachers have a different view from the spirit of religious moderation itself. This research attempts to describe the ‘voice from below’ of PAI teachers who are an integral part of the Ministry of Religious Affairs, in understanding religious moderation in Pekanbaru. Data were collected through in-depth interviews with several PAI teachers at the junior high school in Pekanbaru City. In general, the views of PAI teachers coincide with the four indicators developed by the Ministry of Religious Affairs; national commitment, tolerance, non-violence and friendliness to local culture. However, there are some important issues that they think should be avoided, namely; wishing Merry Christmas; giving space for the Shia and Ahmadiyya religions; and the obligation to wear hijab for adult women.